ACTH regulation of mitochondrial acyl-CoA thioesterase activity in Y1 adrenocortical tumour cells - Castilla Lozano, Maria del Rocio (2002)
We have previously purified and cloned a phosphoprotein, Arachidonic acid-Related Thioesterase Involved in Steroidogenesis (ARTISt), involved in steroid synthesis through Arachidonic Acid (AA) release. Arachidonic acid-related thioesterase involved in steroidogenesis resulted to be a member of a new family of acyl-CoA thioesterases. The protein was identified by its biocapacity to increase mitochondrial steroidogenesis in a cell free bioassay. In the present study we measure the activity of ARTISt using arachidonoyl-CoA (AA-CoA) as substrate. We demonstrate that ACTH significantly stimulates endogenous mitochondrial thioesterase activity as early as 5 min after ACTH stimulation of Y1 cells. Nordihydroguaiaretic acid (NDGA), an inhibitor of AA release known to affect steroidogenesis, affects the in vitro activity of recombinant ARTISt and also the endogenous mitochondrial acyl-CoA thioesterases. ACTH activation of the enzyme protected ARTISt to the inhibitory effect of NDGA. These results show that an enzyme that release AA from AA-CoA can be regulated in intact cells by steroidogenic hormones.